Fruits in colonia paintings from chile: symbolism more than decoration. (2013)
Fruits played a significant allegorical role within religiouspainting in Colonial Chile. Indeed, this is particularlyvalid if we refer to their presence inside religious painting,where having the opportunity to enter a sacredspace they showed their dignity and the chance to exaltthe daily activities where their present.